EFFECT OF RESPIRATORY DEPRESSION ON ORGANISM FUNCTIONALITY IN CYCLING IN TRIATHLON - Siminaitis, Igors; Čupriks, Leonīds; Čuprika, Aleksandra (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
“Oxygen intake”, “Hypoxia”, “Respiratory muscles training”: are very well known terms in now-a-day sports. That is why the goal of the research is to investigate the effects of the lack of oxygen on an organism’s functionality in the low season preparation term within the cycling stage of triathlon. Nine healthy active triathletes (males n=9), age (20 ± 7 years), competitive at national and international level, were trained in the equal conditions using Spinning bikes in the same room (22 °C ± 2.4 °C and 82 ± 4 % RH), at the same time, at the same cadence (100 revolutions ± 5 rev.) and performing the same exercises. All participants had 4 monocycles pre-experimental preparation (PP). Followed by 12 monocycles (hypoxia training – HT) as a part of a monthly microcycle. During a 60 min session one group was using Ultrabreathe, another group was using the Elevation Mask 2.0 and the last group didn’t use any device performing as a control group. After another 4 monocycles for recovery (R). Data was collected at the end of each phase-PP (4 monocycles in one week), in the middle and at the end of phase-HT (8-monocycles using Elevation Mask 2.0 and Ultrabreathe devices) and the end of phase-R (4-monocycles with no respiration effort). Maximal oxygen consumption (VO2max), Lactate (LA), cadence power (W) and heart rate (HR) was recorded and collected as part of the research. All were measured in laboratory conditions using KORR CardioCoach gas analyzing system for VO2max, cadence power was measured by the Monark LC4R ergometer bike, whereas blood samples were collected for lactate using the COBAS Accutrend Plus device, heart rate data was measured by the POLAR H7 heart rate belts and POLAR Power Flow system. The performances expressed changes in all four parameters on all stages of the experiment. Maximal oxygen consumption showed an increase in two groups who were using the respiratory depression devices after 8 monocycles –by 4,35 and 3,01% respectively, and by the end of the experiment the total difference was - 3,74 and 0,82 % respectively. Improvements were also defined in the level of increase in lactate and maximum cadence power. There was a power increase in the two groups who were using the respiratory depression devices after 8 monocycles - 3,92 and 1,57% respectively, and by the end of experiment the total difference was - 3,57 and 0,87 % respectively. All this data shows us the positive effects of hypoxial training.